The SIRT2 Pathway Is Involved in the Antiproliferative Effect of Flavanones in Human Leukemia Monocytic THP-1 Cells - Caterina Russo; Alessandro Maugeri; Laura De Luca; Rosaria Gitto; Giovanni Enrico Lombardo; Laura Musumeci; Giovambattista De Sarro; Santa Cirmi; Michele Navarra (Biomedicines, 2022)
Acute myeloid leukemia (AML) represents the most alarming hematological disease for adults. Several genetic modifications are known to be pivotal in AML; however, SIRT2 over-expression has attracted the scientific community’s attention as an unfavorable prognostic marker. The plant kingdom is a treasure trove of bioactive principles, with flavonoids standing out among the others. On this line, the aim of this study was to investigate the anti-leukemic properties of the main flavanones of Citrus spp., exploring the potential implication of SIRT2. Naringenin (NAR), hesperetin (HSP), naringin (NRG), and neohesperidin (NHP) inhibited SIRT2 activity in the isolated recombinant enzyme, and more, the combination between NAR and HSP. In monocytic leukemic THP-1 cells, only NAR and HSP induced antiproliferative effects, altering the cell cycle. These effects may be ascribed to SIRT2 inhibition since these flavonoids reduced its gene expression and hampered the deacetylation of p53, known sirtuin substrate, and contextually modulated the expression of the downstream cell cycle regulators p21 and cyclin E1. Additionally, these two flavanones proved to interact with the SIRT2 inhibitory site, as shown by docking simulations. Our results suggest that both NAR and HSP may act as anti-leukemic agents, alone and in combination, via targeting the SIRT2/p53/p21/cyclin E1 pathway, thus encouraging deeper investigations.